Fibroadenoma in axillary accessory breast: a systematic review of the literature - Oliveira Filho, Luiz Carlos Navarro de; Oliveira, Leonardo Salazar Portes Navarro de; Varella, Maria Luísa Navarro; Vieira, René Aloisio da Costa; Oliveira, Luiz Carlos Navarro de (Mastology, 2026)
Introduction: Axillary accessory breast is a benign condition for which surgery is performed based on the patient’s wish. However, accessory breast tissue may be affected by neoplasia, requiring diagnosis and resection. Fibroadenoma represents the main etiology. Objective: This study aimed to provide a better understanding of the imaging characteristics, differential diagnoses, and clinical and surgical treatment options for this pathology. Methods: A systematic literature review was conducted using the PICOS (patient/population, intervention, comparison, outcome, study design) and the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) methodologies to evaluate reported cases in the literature. The databases searched included PubMed and LILACS, without restrictions on date or language. The terms used were: (“Axilla” [Mesh] OR accessory breast) AND (“Fibroadenoma” [Mesh]). Results: The PubMed literature contained 45 articles, and LILACS contained one article (also presented in PubMed). The medical literature reported only 43 cases of fibroadenoma in the axillary accessory breast, and two more cases were added. Despite fibroadenoma being the most common benign breast neoplasm, fewer than 50 cases have been described in the literature regarding this condition. Due to its rarity, clinical suspicion is low, and imaging findings are atypical. This condition should be considered in the differential diagnosis of benign, malignant, or metastatic axillary pathologies. The patients underwent surgical resection of the accessory breasts. Conclusion: Conservative management of axillary accessory breast tissue is possible, although ectopic breasts may be affected by neoplasms. In cases of suspected malignancy, investigation follows the same clinical protocol used for breasts in normal anatomical positions, ensuring timely diagnosis. When fibroadenoma occurs in the accessory breast, careful observation is the safest approach and should be conducted in conjunction with the evaluation of the primary breast tissue.